The Second Life of Natural Killer (NK) Cells - Joseph C. Sun (Frontiers Research Topics, 2018)
Natural Killer (NK) cells are innate lymphocytes, now recognized as members of a larger family of "Innate lymphoid cells" (ILCs). Both murine and human NK cells are well characterized effector cells with cytotoxic as well as cytokine production ability which mainly react in response to microbial and cell stress stimuli, thus playing a central role in the defense against pathogen infection, in tumor surveillance and in regulating immune homeostasis. Despite these established concepts, our understanding of the complexity of NK cells, also in view of their developmental and functional relationship with other ILC subsets, is only recently emerging. This Research Topic highlights the recent advances in NK cell (and ILC) research in human and mouse from basic research to clinical applications.